Is the association between maternal alcohol consumption in pregnancy and pre‐school child behavioural and emotional problems causal? Multiple approaches for controlling unmeasured confounding. (10th March 2019) - Lund, Ingunn Olea; Moen Eilertsen, Espen; Gjerde, Line C.; Røysamb, Espen; Wood, Mollie; Reichborn‐Kjennerud, Ted; Ystrom, Eivind
Abstract: Background and aims: Hazardous drinking (i.e. alcohol consumption that places drinkers at risk for adverse health outcomes) during pregnancy is associated with adverse child outcomes. To address whether the associations are causal, we aimed to estimate the effect of maternal hazardous drinking during the first trimester on offspring emotional and behavioural problems throughout the pre‐school age. We adjusted for: (1) measured confounding (e.g. smoking), (2) familial risk factors by sibling control design and (3) non‐shared environmental risk factors by using hazardous drinking the 3 months before pregnancy as an instrumental variable. Design: Prospective cohort study. Participants were recruited between 1999 and 2009 at ultrasound examination offered to all pregnant women in Norway. Data were collected during the 17th and the 30th weeks of gestation, and when the children were aged 1.5, 3 and 5 years. Setting: Norway, 1999–2015. Participants: The sample consisted of 14 639 mothers with 25 744 offspring siblings from the Norwegian Mother and Child Cohort Study. Measurements: Respondents self‐reported on: alcohol consumption, children's emotional problems (i.e. emotional reactive, anxiety/depression, somatic complaints) and children's behavioural problems (i.e. attention and aggressive behaviour) throughout pre‐school age. We used longitudinal latent growth curve models to estimate the effect of maternal drinking during the first trimester on offspring emotional and behavioural problems. Findings: Most associations were strongly reduced after controlling for both familial and measured environmental risk factors. After adjustment, exposed children were more emotionally reactive [β = 2.33; 95% confidence interval (CI) = 0.13–4.53] and had more somatic complaints (β = 1.93; 95% CI = 0.09–3.77) at age 3, but not at age 5. Exposed children were less aggressive than unexposed siblings at age 5 (β = −2.27; 95% CI = –4.02 to –0.52). Conclusions: Children exposed to their mothers' hazardous drinking during the first trimester appear to be more emotionally reactive and have more somatic complaints at age 3, but not at age 5, and are less aggressive at age 5 compared with unexposed siblings.